Foreign-body Impaction in Oropharynx Region - Mohammad Imran Khan; Abhisheik Khare; Khushboo Arif; Abdullah Nasir (Wolters Kluwer Medknow Publications, 2024)
Fish bone impaction in the oral cavity and oropharynx region involving the palatopharyngeus, tonsillar fossa, base of the tongue, and migration into the gastrointestinal tract has all the possibilities of causing no symptoms or life-threatening outcomes. Foreign-body impaction is very common in adults, especially in coastal areas and the eastern region of the India. The delay in the removal of fish bone can cause serious complications and rarely life-threatening consequences. Radiographs and conventional computed tomography may be needed in migrated fish bone in deeper soft tissue and further downward displacement in the gastrointestinal tract.